Perceptual Experience and Seeing-as - Kalpokas, Daniel Enrique (2015)
According to Rorty, Davidson and Brandom, to have an experience is to be caused by our senses to hold a perceptual belief. This article argues that the phenomenon of seeing-as cannot be explained by such a conception of perceptual experience. First, the notion of experience defended by the aforementioned authors is reconstructed. Second, the main features of what Wittgenstein called “seeing aspects” are briefly presented. Finally, several arguments are developed in order to support the main thesis of the article: seeing-as cannot be explained by the conception of experience defended by Rorty, Davidson and Brandom.